\(x^3-5x=2x^2-10\)
\(\Leftrightarrow x^3-2x^2-5x+10=0\)
\(\Leftrightarrow x^2\left(x-2\right)-5\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x^2-5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x^2-5=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\pm\sqrt{5}\end{matrix}\right.\)
\(x^3-5x=2x^2-10\)
\(\Leftrightarrow x^2\left(x-2\right)-5\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x-\sqrt{5}\right)\left(x+\sqrt{5}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\sqrt{5}\\x=-\sqrt{5}\end{matrix}\right.\)